Freshwater fish diversity and its conservation status in different water bodies of Nepal - Khatri, Kumar; Jha, Bibhuti Ranjan; Gurung, Smriti; Khadka, Udhab Raj (Nepal Journal of Environmental Science, 2020)
This review describes the current status of freshwater fish diversity, their IUCN categories and threats to fish fauna in Nepal. The freshwater systems of the country are known to harbor over 220 fish species, thereby indicating a rich ichthyofaunal diversity. However, this number varies from author to author. Cyprinidae is the most common and dominant taxon. A total of 15 endemic and 15 exotic fish species have been reported. A total of 34 fish species have been listed under the IUCN Red List threatened categories. Major threats to fish include damming and pollution. Fish diversity studies have mainly focused on inventories only. Studies focusing on river longitudinal aspects, the inclusion of spatio-temporal aspects, and rigorous taxonomic studies combined with genetic studies are crucial to develop strategic conservation measures of fish fauna in Nepal.